Parathyroid cyst of the thymus. - McCluggage, W. G. (1995)
A case is described of primary hyperparathyroidism in a patient with both a parathyroid cyst within the thymus gland and a concomitant parathyroid adenoma. The parathyroid adenoma contained microcystic areas of degeneration, and it is thought that the parathyroid cyst reflected degenerative change in a pre-existing adenoma. Parathyroid cyst should be considered in the differential diagnosis of cystic lesions within the thymus. Fine needle aspiration and parathyroid hormone assay on cyst fluid may provide a preoperative diagnosis.